Speech perception.[article]. - Samuel Arthur G.
Speech perception has been studies for over a half century. During this time, one subfield has examined perception of phonetic information independent of its contribution to word recognition. Theories in this subfield include ones that are based on auditory properties of speech, the motor commands involved in speech production, and a Direct Realist approach that emphasizes the structure of the information reaching the perceiver. A second subfield has been less concerned with the acoustic-phonetic properties of speech and more concerned with how words are segmented and recognized. In this subfield, there has been a focus on the nature of communication among different levels of analysis (e.g., phonetic and lexical). In recent years, there has been a growing appreciation of the need to understand how the perceptual system dynamically changes in order to allow listeners to successfully process the variable input and new words that they constantly encounter. - (from the author)